Microplastics and anthropogenic debris in rainwater from Bahia Blanca, Argentina - Villafañe, A. Belén (2023)
Concern about atmospheric microplastic (MP) contamination has increased in recent years. This study assessed the abundance of airborne anthropogenic particles, including MPs, deposited in rainfall in Bahia Blanca, southwest Buenos Aires, Argentina. Rainwater samples were collected monthly from March to December 2021 using an active wet-only collector consisting of a glass funnel and a PVC pipe that is only open during rain events. Results obtained show that all rain samples contained anthropogenic debris. The term “anthropogenic debris” is used to refer to the total number of particles as not all the particles found could be determined as plastic. Among all the samples, an average deposition of 77 ± 29 items (anthropogenic debris) m⁻²d⁻¹ was found. The highest deposition was observed in November (148 items m⁻²d⁻¹) while the lowest was found in March (46 items m⁻²d⁻¹). Anthropogenic debris ranged in size from 0.1 mm to 3.87 mm with the most abundant particles being smaller than 1 mm (77.8%). The dominant form of particles found were fibers (95%), followed by fragments (3.1%). Blue color predominated (37.2%) in the total number of samples, followed by light blue (23.3%) and black (21.7%). Further, small particles (<2 mm), apparently composed of mineral material and plastic fibers, were recognized. The chemical composition of suspected MPs was examined by Raman microscopy. The analysis of μ-Raman spectra confirmed the presence of polystyrene, polyethylene terephthalate, and polyethylene vinyl acetate fibers and provided evidence of fibers containing industrial additives such as indigo dye. This is the first assessment of MP pollution in rain in Argentina.